ASSESSMENT METHOD OF THE REPAIRED AIRCRAFT COMPOSITE WING PANEL WITH DISCRETE-SOURCE DAMAGE - CHEN XiangMing; ZHANG AYing; CHAI YaNan; LIU HongWu; WANG LiLi; YU Fei (Jixie qiangdu)
The progressive damage analysis technique was studied by using finite element method and test validation of the repaired aircraft wing composite panel with discrete-source damage. Firstly,an analysis model adopting the two dimensional LaRC05 and B-K failure criteria was established to indentify the initial damage of composite ply and interface. Then,a user defined subroutine UMAT of material failure criteria and degradation rule based on commercial software ABAQUS was programmed and the load carrying capacity of the repaired aircraft wing composite panel was analyzed. The numerical results indicated that: the FEM analysis method presented in this paper was viable for the large-scale bolted repair structure. The comparison between analysis and test indicates that the load carrying capacity and failure mode of numerical results agree well with test results. The errors of predicted load carrying capacity are within 5%.